2007
DOI: 10.1016/j.geoderma.2006.08.020
|View full text |Cite
|
Sign up to set email alerts
|

Effects of two soil reclamation techniques on the distribution of the organic N compounds in a 15N labelled burnt soil

Abstract: The evolution of the soil organic-N forms and their bio-availability was studied in a 15 N labelled and burnt soil (BLS) after two successive reclamation steps under greenhouse conditions: a 3-month growing period of Lolium, without (BLS-L) or with poultry manure addition (4 and 8 Mg ha − 1 : BLS + PM4-L and BLS + PM8-L), followed by a 12-month growing phase of pine seedlings (BLS-P, BLS + PM4-P and BLS + PM8-P). The results were compared with those obtained for the homologous labelled unburnt soil (LS, LS-L a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Among organic amendments, Villar et al (1998) found better plant growth rates in a burnt soil amended with poultry manure as compared with cattle slurry or sewage sludge; moreover, Castro et al (2000) reported that poultry manure greatly enhanced gramineous plant growth even at low doses (1-4 Mg ha -1 ) enough to ensure its technical, economical and ecological applicability on burnt forest ecosystems. However, this technique is insufficient to recover the pre-fire status and distribution of soil organic N (Castro et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Among organic amendments, Villar et al (1998) found better plant growth rates in a burnt soil amended with poultry manure as compared with cattle slurry or sewage sludge; moreover, Castro et al (2000) reported that poultry manure greatly enhanced gramineous plant growth even at low doses (1-4 Mg ha -1 ) enough to ensure its technical, economical and ecological applicability on burnt forest ecosystems. However, this technique is insufficient to recover the pre-fire status and distribution of soil organic N (Castro et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…This information is especially important considering that recently Castro et al (2007) found that revegetation and PM addition, even jointly used, were unable to reduce the huge differences observed between the burnt and the unburnt soils for N fractions that accounted for more than 80% of the soil organic N.…”
Section: Introductionmentioning
confidence: 99%
“…Among tree nutrients, N is very important because: (a) it is the major growth‐limiting mineral element for higher plants;17 and (b) its cycle is strongly altered by wildfires, which reduce dramatically the labile soil‐N reserves that are the major source of N for plants 18, 19. Therefore, from the N cycle point of view, evaluating accurately the medium‐term efficacy of the burnt soil restoration techniques is necessary; the usefulness of 15 N tracers for this task has been recently recognized 11, 12, 19–21…”
mentioning
confidence: 99%